2018
DOI: 10.1038/s41598-018-21730-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal avalanche dynamics indicates different universality classes in neuronal cultures

Abstract: Neuronal avalanches have become an ubiquitous tool to describe the activity of large neuronal assemblies. The emergence of scale-free statistics with well-defined exponents has led to the belief that the brain might operate near a critical point. Yet not much is known in terms of how the different exponents arise or how robust they are. Using calcium imaging recordings of dissociated neuronal cultures we show that the exponents are not universal, and that significantly different exponents arise with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 32 publications
(49 reference statements)
8
51
1
Order By: Relevance
“…Comparative studies of the functional benefits of the different critical points promise to be an interesting topic of future research, not only for the goal of basic understanding of nervous systems, but also for augmented machine learning efficiency based on critical dynamics 56,57 . Early and late criticality bear an intriguing similarity to the two different universality classes for cultured neuronal networks found by Yaghoubi et al 28 . In their study, the two universality classes were found in two different types of neuronal cultures that either had or didn't have an acid metabolite 5M4Hfolate in the culture medium.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Comparative studies of the functional benefits of the different critical points promise to be an interesting topic of future research, not only for the goal of basic understanding of nervous systems, but also for augmented machine learning efficiency based on critical dynamics 56,57 . Early and late criticality bear an intriguing similarity to the two different universality classes for cultured neuronal networks found by Yaghoubi et al 28 . In their study, the two universality classes were found in two different types of neuronal cultures that either had or didn't have an acid metabolite 5M4Hfolate in the culture medium.…”
Section: Discussionsupporting
confidence: 66%
“…The two regimes-we again refer to them as the "early" and "late" criticality, due to their temporal occurrence-bear strong similarities to the two critical regimes exhibited above in our theoretical model and to what ref. 28 found experimentally. Below we present the analysis of data from primarily two selected cultures with conditioned media ("Cultures 1-2", see our Supplementary Notes for additional cultures).…”
Section: Figmentioning
confidence: 84%
See 1 more Smart Citation
“…In particular, the avalanche size exponent τ 1.5 originally observed by Beggs and Plenz [2] coincides with any model in the MF-DP universality class. But other experimental setups have revealed different exponents [9,30,35]. Likewise, models with different topologies or ingredients in their dynamics might give rise to exponents which differ from those of MF-DP.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, here we consider a fully connected system. However, it has been shown [62] that network topology has an effect on power laws, and thus models with weaker connections can produce distributions with exponents significantly larger than 1.25, even with additional input. Our result is a first step towards understanding the diversity of power-law exponents reported in the neuronal data.…”
Section: Resultsmentioning
confidence: 99%